2019
DOI: 10.1186/s12889-019-7059-8
|View full text |Cite
|
Sign up to set email alerts
|

Single transitions and persistence of unemployment are associated with poor health outcomes

Abstract: Background Although job loss has been associated with decline in health, the effect of long term unemployment is less clear and under-researched. Furthermore, the impact of an economic recession on this relationship is unclear. We investigated the associations of single transitions and persistence of unemployment with health. We subsequently examined whether these associations are affected by the latest recession, which began in 2008. Methods In total, 57,911 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…More recent evidence supports the assumption that employment benefits prevail for people with and without mental illness (8)(9)(10)(11). Conversely, the negative effects of unemployment may be particularly profound for people with mental illness (12,13).…”
Section: Introductionmentioning
confidence: 75%
“…More recent evidence supports the assumption that employment benefits prevail for people with and without mental illness (8)(9)(10)(11). Conversely, the negative effects of unemployment may be particularly profound for people with mental illness (12,13).…”
Section: Introductionmentioning
confidence: 75%
“…2. Sociodemographic characteristics of patients visiting the emergency department based on their social determinants of health (SDOH) stratum (based on SDOH index score: lower impact stratum -index score 0-5; middle impact stratum -index score 6-10; and higher impact stratum -Index score [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that there is a higher prevalence of poor health and mortality in the unemployed. [11][12][13] In homeless individuals, lack of resources makes it difficult to maintain health and navigate the health system, and makes them more likely to use the ED than the general population. [14][15][16][17] Food insecurity, lower education levels, and limited access to primary care have all been found to increase ED utilization as well.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“…Another aspect to consider is short-term as opposed to long-term unemployment, where the latter is largely associated with worse health [3,6,[16][17][18]. While individuals who had experienced repeated unemployment compared to those who had never been unemployed reported significantly worse mental health and lower life satisfaction [19], individuals who had experienced single unemployment compared to the other groups (i.e., repeated unemployment or no experience at all) only significantly differed in their satisfaction with income and employment [20].…”
Section: Short-versus Long-term Unemploymentmentioning
confidence: 99%